TCP/IP sockets in C practical guide for programmers - Donahoo, Michael J.; Calvert, Kenneth L. (San Francisco : Morgan Kaufmann Publishers, 2001)
For example code from the text, Winsock adaptations of text code, sample programming exercises and more, click on the grey "COMPANION SITE" button to the right. Note: This title was formerly known as Pocket Guide to TCP/IP Socket Programming in C, ISBN 1-55860-686-6. TCP/IP Sockets in C: Practical Guide for Programmers is a quick and affordable way to gain the knowledge and skills you need to develop sophisticated and powerful networked-based programs using sockets. Written by two experienced networking instructors, this book provides a series of examples that demonstrate basic sockets techniques for clients and servers. Using plenty of real-world examples, this book is a complete beginner's guide to socket programming and a springboard to more advanced networking topics, including multimedia protocols. *Concise, no-nonsense explanations of issues often troublesome for beginners, including message construction and parsing. *Comprehensive example-based coverage of the most important TCP/IP techniques-including iterative and concurrent servers, timeouts, and asynchronous message processing. *Includes a detailed, easy-to-use reference to the system calls and auxiliary routines that comprise the sockets interface. *A companion Web site provides source code for all example programs in both C and WinSock versions, as well as guidance on running the code on various platforms.
I Tutorial -- 1 Introduction -- 2 Basic Sockets -- 3 Constructing Messages -- 4 Using UDP Sockets -- 5 Socket Programming -- 6 Under The Hood -- 7 Domain Name Service -- II API Reference -- Data Structures -- Socket Setup -- Socket Connection -- Socket Communication -- Socket Control -- Binary/String Conversion -- Host and Service Information.
Rev. ed. of: The pocket guide to TCP/IP sockets. c2001.
Includes bibliographical references and index.
Keywords: Application program interfaces (Computer software); TCP/IP (Computer network protocol); C (Computer program language) -- Study and teaching; Electronic books